2000
DOI: 10.2337/diabetes.49.6.1042
|View full text |Cite
|
Sign up to set email alerts
|

Age-related patterns of the clustering of cardiovascular risk variables of syndrome X from childhood to young adulthood in a population made up of black and white subjects: the Bogalusa Heart Study.

Abstract: The age-related patterns of clustering of cardiovascular risk variables of Syndrome X from childhood to adulthood were examined in a community-based sample of black and white children (aged 5-10 years, n = 2,389), adolescents (aged 11-17 years, n = 3,371), and young adults (aged 18-37 years, n = 2,115). In the analysis of clustering, insulin resistance index, BMI, triglycerides/ HDL cholesterol ratio, and mean arterial pressure were used either as categorical variables (age-, race-and sexspecific values >75th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
134
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(152 citation statements)
references
References 44 publications
11
134
1
6
Order By: Relevance
“…12 Consequently, very recent reports discussed the possibility of discouraging the growing use of the term 'metabolic syndrome', in favor of considering and subsequently treating each component separately. 9,11,13,14 Several authors have tried to give different names to the MS, adding components to improve the validity of the overall diagnosis, 13,14,16,36 but these may simply be causing confusion in Metabolic risk-factor clustering estimation in children P Brambilla et al daily clinical practice. 13,14 In light of this background, and taking into account the major and minor concerns discussed above, we argue that pediatricians need to consider a novel approach to assessing obese children, and should not simply derive or adapt definitions from adults.…”
Section: Minor Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Consequently, very recent reports discussed the possibility of discouraging the growing use of the term 'metabolic syndrome', in favor of considering and subsequently treating each component separately. 9,11,13,14 Several authors have tried to give different names to the MS, adding components to improve the validity of the overall diagnosis, 13,14,16,36 but these may simply be causing confusion in Metabolic risk-factor clustering estimation in children P Brambilla et al daily clinical practice. 13,14 In light of this background, and taking into account the major and minor concerns discussed above, we argue that pediatricians need to consider a novel approach to assessing obese children, and should not simply derive or adapt definitions from adults.…”
Section: Minor Concernsmentioning
confidence: 99%
“…12 The parameters of the MS develop in stages, according to age-related changes in obesity, so the full syndrome cannot generally be expressed at an early age. 36 Moreover, it is fundamental to take into account that in children and adolescents, the pathophysiological basis and characteristics of the MS are also influenced by growth and puberty, 36,37 and not only by gender, ethnicity and body composition as they are in adults. The available literature has focused on the assessment of the MS in overweight and obese children; however, we suspect that a clustering of risk-factors can also be observed in normal-weight children and adolescents, 18,22 as already shown in adults.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that there is a clustering of cardiovascular disease-risk factors, such as dyslipidemia, high blood pressure, and obesity from childhood to young adolescence, which is influenced by age-related changes in obesity. 38 Obesity in children and adolescents is associated with a characteristic pattern of increased blood lipids, consisting of elevated LDL-C and triglycerides and low HDL-C levels. 7 This pattern is confirmed by the present study (Figure 1), where baseline triglyceride levels are elevated in always overweight subjects compared to never overweight, whereas HDL-C levels were significantly lower.…”
Section: Short-term Overweight Predictors Sc Savva Et Almentioning
confidence: 99%
“…The incidence of childhood metabolic syndrome (MetS), which is closely related to insulin resistance, is defined as a clustering of abdominal obesity, hypertension, dyslipidemia and glucose intolerance and is increasing around the world, including in Korea [2]. The clustering of metabolic risk factors begins in childhood [3], and these multiple risk factors tend to persist from childhood into adulthood [4]. Childhood MetS is a risk factor for MetS, cardiovascular diseases and Submitted Jun.…”
mentioning
confidence: 99%